2003
DOI: 10.1034/j.1600-0773.2003.920104.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Permeability of Blood‐Brain Barrier Induced by Repeated Administration of Endothelin‐1 in Dogs and Rats

Abstract: Abstract:The effects of intracisternal administration of endothelin-1 on blood-brain barrier permeability were examined in dogs and rats. Single doses of endothelin-1 elevated blood-brain barrier permeability about two times compared with control groups in both species. However, repeated dosing with endothelin-1 at a 24 hr intervals caused a highly enhanced disruption of blood-brain barrier permeability in dogs, but not in rats, whereas the repeated administration with a 48 hr interval markedly increased the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…For example, ET-1 interactions with endothelin A receptors may lead to disruption of the blood-brain barrier (41). HIV-infected astrocytes are most often present at the blood-brain barrier or close to brain capillaries (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ET-1 interactions with endothelin A receptors may lead to disruption of the blood-brain barrier (41). HIV-infected astrocytes are most often present at the blood-brain barrier or close to brain capillaries (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…The literature contains conflicting reports as to the effects of ET-1 on brain capillary permeability. Thus, injection of ET into the brain has been reported to increase permeability (Narushima et al, 2003) or to have no significant effect (Hughes et al, 2003). In these in vivo studies, permeability measurements were made after many hours to days of ET-1 treatment.…”
Section: Regulation Of P-glycoprotein At the Blood-brain Barrier 391mentioning
confidence: 99%
“…In dogs, treatment with EDN1 resulted in increased permeability of the blood-brain-barrier; treatment with an EDN1 receptor antagonist reversed this and also ameliorated EAE in rats. 20,21 Furthermore, inhibition of the EDN1 receptor by antagonists or gene knockdown reduced the transmigration of monocytes through brain endothelium in vitro. 22 In this study we found increased mRNA levels of EDN1 in the CNS-infiltrating leukocytes from patients compared with controls, which are in line with the previous observations of increased plasma and CSF levels of EDN1 in MS. 23,24 Together, these results indicate that local production of EDN1 in the infiltrating leukocytes may be important for the passage of leukocytes across the bloodbrain-barrier in MS. CXCL11 is a potent chemoattractant for activated T-cells and also a ligand for CXCR3.…”
Section: Discussionmentioning
confidence: 99%